PENDAMPINGAN PENYUSUNAN LAPORAN KEUANGAN KOMUNITAS USAHA “YATIM MANDIRI BUNDA BISA” - Latifah, Eny; Agustina, Wa Ode (Jurnal Pengabdian Masyarakat Berkarya, 2024)
Community Service by providing assistance in compiling The purpose of this community service activity is to provide understanding and knowledge to the Yatim Mandiri Buunda Bisa community in compiling financial reports based on SAK EMKM so that they understand and are able to apply financial reporting. The methods used are lectures/presentations, discussions/questions and answers, and mentoring of partners who are dominated by mothers and young women who are active in creative activities of Micro, Small and Medium Enterprises. The results achieved are that partners have basic knowledge in analyzing and recording financial transactions that occur in their business entities and partners have skills in compiling Yatim Mandiri Bunda Bisa financial report documents in accordance with applicable accounting standards